Influence Of Palm Oil Fuel Ash As Supplementary Binder On Properties Of Polymer Modified Concrete - Zakaria, Nurhana (2014)
Malaysia being the second largest world's palm oil producer has led to the mounting up of the waste produced from this industry and has caused environmental problem. Palm Oil Fuel Ash (POFA) is an agricultural waste from palm oil mill that has been proven to have pozzolanic properties which can enhance the properties of concrete when used as supplementary cementitious material in concrete. POFA used in this research was processed by means of sieving, grinding and subjecting it to heat treatment of 500±50°C for l hour before undergoing the second grinding stage. The raw and processed POFA were characterized to confirm its pozzolanic characteristics. Previous researchers have recommended the use of POFA in concrete especially for strength enhancement. The use of SBR as polymer modifier in concrete has been introduced since long time ago. Although the addition of polymer modifier in concrete improved its durability properties, however, it did not enhance the compressive strength of the concrete significantly. The main objective of this research is to observe the effect of using POFA as partial cement replacement on the engineering and transport properties of Polymer Modified Concrete (PMC).